Research on Development Strategies for Social Work in the Context of Social Management System Reform - Liu, Jiachen (International Journal of Humanities and Social Science, 2025)
At present, China is at a critical juncture in the deepening transformation of its social management system, as the traditionally administration-dominated model gradually shifts toward a multi-stakeholder collaborative governance approach. This profound transformation offers significant opportunities for the development of social work, while also posing unprecedented challenges. Social work is increasingly expected to address complex social needs and contribute to improving the efficiency of public services. However, in practice, the pace of professional service development has not yet fully aligned with ongoing institutional reforms, and the tension between resource constraints and the demand for improved efficiency persists. It has therefore become increasingly urgent to explore a development model for social work that is closely linked to the reform agenda, applicable to China’s specific context, and capable of supporting the modernization of social governance.